Quiescent hepatic stellate cells functionally contribute to the hepatic innate immune response via TLR3. - Caroline L Wilson; Jelena Mann; Meagan Walsh; Maria J Perrugoria; Fiona Oakley; Matthew C Wright; Chiara Brignole; Daniela Di Paolo; Patrizia Perri; Mirco Ponzoni; Michael Karin; Derek A Mann (PLoS ONE)
Toll-like Receptor 3 (TLR3) is a pathogen pattern recognition receptor that plays a key role in innate immunity. TLR3 signalling has numerous functions in liver, both in health and disease. Here we report that TLR3 is expressed by quiescent hepatic stellate cells (HSC) where it functions to induce transcription and secretion of functional interferons as well as a number of other cytokines and chemokines. Upon transdifferentiation into myofibroblasts, HSCs rapidly loose the ability to produce interferon gamma (IFNγ). Mechanistically, this gene silencing may be due to Polycomb complex mediated repression via methylation of histone H3 lysine 27. In contrast to wild type, quiescent HSC isolated from tlr3 knockout mice do not produce IFNγ in response to Poly(I∶C) treatment. Therefore, quiescent HSC may contribute to induction of the hepatic innate immune system in response to injury or infection.